Fluorescent Sensing of Ciprofloxacin and Chloramphenicol in Milk Samples via Inner Filter Effect and Photoinduced Electron Transfer Based on Nanosized Rod-Shaped Eu-MOF - Yue, Xiaoyue; Wu, Chaoyun; Zhou, Zijun; Fu, Long; Bai, Yanhong (Foods, 2022)
Rapid, facile, and accurate detection of antibiotic residues is vital for practical applications. Herein, we designed a sensitive, visual, and rapid analytical method for sensitive detection of ciprofloxacin and chloramphenicol based on a nanosized rod-shaped Europium metal organic framework (Eu-MOF). The fluorescent Eu-MOF was firstly synthesized by a simple synthetic route at room temperature, which displays a red emission. The mechanisms of detecting ciprofloxacin and chloramphenicol were confirmed to be the inner filter effect (IFE) and photoinduced electron transfer (PET). Under the optimized experimental conditions, the detection limits of the developed method for ciprofloxacin and chloramphenicol detection were 0.0136 and 3.16 μM, respectively. Moreover, the sensor was effectively applied for quantitative determination of ciprofloxacin and chloramphenicol milk samples with satisfactory recoveries of 94.5–102% and 97–110%, respectively. This work developed a new method for rapid detection of ciprofloxacin and chloramphenicol residues. In addition, the established method has potential practical application value for on-site safety regulation on antibiotic residues in animal-derived food.